Conventional marketing communication tools for residential products in digital era - Briandana, Rizki; Dwityas, Nindyta Aisyah (Technium Social Sciences Journal, 2020)
This study aims to determine the marketing communication strategies, especially the use of conventional advertising and personal sales carried out by the company in the digital era. Amidst the widespread use of the latest and most sophisticated communication channels, Indonesia's property company is still consistent in using conventional promotional tools to reach its consumers. The method used in this research is a case study within-depth interview data collection techniques. The results showed that the company carries out advertising activities only through outdoor print media and carries out personal selling activities. In general, the company's goal-setting phase still focuses on sales direction and targets. The specified objectives also become one of the important benchmarks in the evaluation phase. These objectives will be reviewed and measured again at the end of the commercialization program carried out within a certain period.